Straight ladder inclined angle in a field environment: the relationship among actual angle, method of set-up and knowledge. Issue 8 (2nd August 2016) - Chang, Wen-Ruey; Huang, Yueng-Hsiang; Chang, Chien-Chi; Brunette, Christopher; Fallentin, Nils
Abstract: Ladder inclined angle is a critical factor that could lead to a slip at the base of portable straight ladders, a major cause of falls from heights. Despite several methods established to help workers achieve the recommended 75.5° angle for ladder set-up, it remains unclear if these methods are used in practice. This study explored ladder set-up behaviours in a field environment. Professional installers of a company in the cable and other pay TV industry were observed for ladder set-up at their worksites. The results showed that the actual angles of 265 ladder set-ups by 67 participants averaged 67.3° with a standard deviation of 3.22°. Although all the participants had training on recommended ladder set-up methods, only 3 out of 67 participants applied these methods in their daily work and even they failed to achieve the desired 75.5° angle. Therefore, ladder set-up remains problematic in real-world situations. Practitioner Summary: Professional installers of a cable company were observed for portable straight ladder set-up at their worksites. The ladder inclined angle averaged 67.3° with a standard deviation of 3.22°, while the recommended angle is 75.5°. Only a few participants used the methods that they learned during training in their daily work.